Director-auditor link and audit quality: the simultaneous effect of auditor-director attachment on audit fees, non-audit services and audit opinion - Malik@Malek, Mazrah (LAP Lambert Academic Publishing, 2012)
Director-Auditor Link and Audit Quality aims to examine the effects of director-auditor link on audit services fee, non-audit services fee and audit opinion. Based on the attachment theory, it is argued that director-auditor link created by interlocking directorates enhances the mutual dependence and trust between the directors and their auditor and this mutuality is expected to influence audit services fee, non-audit services purchased from auditor and audit opinion. Analyses are conducted using data of 759 listed companies on the Bursa Malaysia in 2007 and a two-stage regression method is employed to accommodate the simultaneous equation model. The results show that director-auditor link has a significant negative relationship with audit services fee and significant positive relationships with non-audit services fee purchased from auditor and the issuance of unqualified audit opinion. Thus, the results provide initial evidence on the importance of reviewing the director-auditor link practices in the business environment.